Natural Triboelectric Generators: Energy Conversion at the Cuticle of Living Plants (Adv. Funct. Mater. 51/2018). (17th December 2018) - Meder, Fabian; Must, Indrek; Sadeghi, Ali; Mondini, Alessio; Filippeschi, Carlo; Beccai, Lucia; Mattoli, Virgilio; Pingue, Pasqualantonio; Mazzolai, Barbara
Abstract : The leaves of living plants are the largest biointerface existing on earth that could now be utilized to generate electricity. In their article number1806689, Fabian Meder, Barbara Mazzolai, and co‐workers investigate how charge generation at the leaf surface occurs and use the effect to construct living plant‐hybrid energy converters for harvesting wind power.